Computational Fluid Dynamics (CFD) Simulation and Comparison for Different Numbers of Baffles to Reduce Concentration Polarization Effects in Membrane Tubes - Ahsan, Muhammad; Hussain, Arshad (Journal of Engineering and Technological Sciences, 2017)
This research shows the use of computational fluid dynamics (CFD) with finite volume method (FVM) to study the species diffusion and mixing characteristics in a tubular membrane filled with vertical baffles. This study exhibits how to set up the FVM for CFD simulation and residence time distribution (RTD) analysis and compare the mixing characteristics of two membrane tubes with a different number of baffles using RTD curves. In this study, the effects of the number of baffles on flow patterns, features and behavior of air were identified completely through computational fluid dynamics (CFD) simulations. In addition, a two-dimensional simulation was implemented to study the effects of steady and unsteady (transient) flow in the tubular membrane. The residence time distribution (RTD) of a tracer in a co-current flow pattern was investigated. For this, the tracer was injected for 1 second into the membrane tubes on a frozen flow field and the concentration variation of the tracer over time was monitored at the outlet.